Role of Ultrasonography in Diagnosing Acute Cholecystitis and Correlation with Intra-operative Findings - Singh, Bal Jaskaran; Kapoor, Sudershan (International Journal of Innovative Research in Medical Science, 2018)
Background: 90-95% of cases of acute cholecystitis are caused due to gall stones, i.e. calculous cholecystitis. Rest of the 5-10% cases are caused without the presence of stones, i.e. acalculous cholecystitis. Diagnosis of acute cholecystitis involves clinical, laboratory, and radiographic findings especially by ultrasonography. The aim of the study is to evaluate role of ultrasonography in diagnosing acute cholecystitis and correlation with intra-operative findings. Material and Methods: The present study was conducted in the Department of Surgery, Govt. Medical College, Amritsar. A sample size of 50 patients was taken who were diagnosed as cases of acute cholecystitis either clinically or radiologically referred to the department. Results: The mean age of presentation was 54.94 years. It was more common in females than males and more common among married females. On USG abdomen, 92% cases had calculous cholecystitis and 8% had acalculous cholecystitis. Intraoperatively, most common finding was adhesions. It was present in 40 patients (95.24%) and increased wall thickness was present in 37 cases (88.09%). The sensitivity and specificity of ultrasonography in our study was 97.62% and 62.5% respectively. Conclusion: The number of patients presenting with acute cholecystitis is increasing because of the increased awareness. With improved healthcare facilities and newer techniques, complications have declined substantially with reduced mortality and morbidity.